The truth is - Ramos, NoNieqa (Carolrhoda Lab, 2019)
"Closed off and grieving her best friend, fifteen-year-old overachiever Verdad faces prejudices at school and from her traditional mother, her father's distance since his remarriage, and her attraction to a transgender classmate." --